SIESGO: Integral System for Social Construction of Risk - Jerez-Ramírez, Deysi O. (2022)
[Introduction]: Understanding risk is the fundamental basis for prevention and building resilience, just as local management is the raw material for actions at the national scale in issues of Disaster Risk Reduction (DRR). Nonetheless, municipalities and local communities in Latin America generally lack specialized systems in locating and understanding the problematic in its different manifestations. [Objective]: Describe and analyze the methodology, structure and criteria used by the Integral System for Social Construction of Risk (SIESGO), as well as the advantages of Geographic Information Systems (GIS) technology as assessment tools for DRR. [Methodology]: Implementation of the National Center for Disaster Prevention of Mexico (CENAPRED) guide (revised and improved) for the evaluation of physical and social vulnerability in a cloud-based GIS that allows the use of geospatial technology for the integral optimization of the process. [Results]: Construction of a system for risk evaluation by automatically calculating the Social Vulnerability Index (SVI) of the study area and its corresponding thematic maps generated through a GaaS (GIS as a Service) application, in interaction with sources of threat. [Conclusions]: Through implementing this solution it is possible to determine not only the location of each of the elements of the risk geosystem, but also to extract the possible relationships that are generated between these elements from the superposition of the information layers. SIESGO is presented as an efficient and easy-to-use tool that configures the ideal way for decision-making and the socialization of relevant information on the subject of interest.